Associations of sarcopenia with graft failure and mortality in patients undergoing living donor liver transplantation. Issue 8 (25th April 2022) - Sim, Ji‐Hoon; Kwon, Hye‐Mee; Kim, Kyung‐Won; Ko, You‐Sun; Jun, In‐Gu; Kim, Sung‐Hoon; Kim, Kyoung‐Sun; Moon, Young‐Jin; Song, Jun‐Gol; Hwang, Gyu‐Sam
Abstract: Recent studies have reported that sarcopenia influences morbidity and mortality in surgical patients. However, few studies have investigated the associations of sarcopenia with short‐term and long‐term graft failure in recipients after living donor liver transplantation (LDLT). In this study, we investigated the associations between sarcopenia and graft failure/mortality in patients undergoing LDLT. We retrospectively examined 2816 recipients who underwent LDLT between January 2008 and January 2018. Cox regression analysis was performed to evaluate the associations between sarcopenia and graft failure/mortality in recipients at 60 days, 180 days, and 1 year and overall. Sarcopenia in the recipient was significantly associated with 60‐day graft failure (adjusted hazard ratio [HR], 1.98; 95% confidence interval [CI], 1.09–3.61; p  = 0.03), 180‐day graft failure (HR, 1.85; 95% CI, 1.19–2.88; p  = 0.01), 1‐year graft failure (HR, 1.45; 95% CI, 1.01–2.17; p  = 0.05), and overall graft failure (HR, 1.42; 95% CI, 1.08–1.87; p  = 0.01). In addition, recipient sarcopenia was associated with 180‐day mortality (HR, 1.88; 95% CI, 1.17–3.01; p  = 0.01), 1‐year mortality (HR, 1.53; 95% CI, 1.01–2.29; p  = 0.04), and overall mortality (HR, 1.43; 95% CI, 1.08–1.90; p  = 0.01). Preoperative sarcopenia was associated with high rates of graft failure and mortality in LDLT recipients. Therefore, preoperative sarcopenia may be a strong predictor of the surgical prognosis in LDLT recipients.